2014
DOI: 10.1002/jnr.23482
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine 251 at the C‐terminus of neuronal glycoprotein M6a is critical for neurite outgrowth

Abstract: Neuronal glycoprotein M6a is involved in neuronal plasticity, promoting neurite and filopodia outgrowth and, likely, synaptogenesis. Polymorphisms in the human M6a gene GPM6A have recently been associated with mental illnesses such as schizophrenia, bipolar disorders, and claustrophobia. Nevertheless, the molecular bases underlying these observations remain unknown. We have previously documented that, to induce filopodia formation, M6a depends on the association of membrane lipid microdomains and the activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 49 publications
1
42
0
1
Order By: Relevance
“…We also found that M6a colocalizes with the lipid raft resident family of Src kinases in different cell types and that M6a phosphorylated at Y251 induces neuritogenesis by recruitment and activation of Src and Akt kinases to the cell surface (Formoso et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…We also found that M6a colocalizes with the lipid raft resident family of Src kinases in different cell types and that M6a phosphorylated at Y251 induces neuritogenesis by recruitment and activation of Src and Akt kinases to the cell surface (Formoso et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…; Formoso et al . ). In support of this hypothesis, in this work, we established the functional role of certain residues in M6a TMDs, which were seen to influence both self‐interaction and stability.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations